Kinetic Study and Simulation of Oleic Acid Esterification over Prepared NaY Zeolite Catalyst - S. Abbas, Ammar; N. Abbas, Rowaida (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Esterification considers the most important reaction in biodiesel production. In this study, oleic acid was used as a suggested feedstock in order to study and simulate production of biodiesel. The batch esterification reaction of oleic acid was carried out at various operating conditions; temperature from 40 to 70 °C, ethanol to oleic acid molar ratio from 3/1 and 6/1 and a reaction time up to 180 min.The catalyst used was prepared NaY zeolite, which is added to the reaction mixture as 2, 5 and 10 wt.% of oleic acid.The results show that the optimum conditions, gives 0.81 conversion of oleic acid, were 6/1 molar ratio of ethanol/oleic acid, 5 wt.% NaY relative to initial oleic acid, 70°C and 60 minutes. The activation energy of the suggested model was 42692 J/mole for forward reaction and 17218 J/mole for backward reaction.